Performance comparison of dispersion compensation using EDC at distinct data rates with distinct photo-detectors devices at receiver. (2022) - Kumar, Ashwani; Verma, Amita; Saini, Raj Kumar; Singh, Inder; Chauhan, Diksha
Abstract: The transmission of the high data rate and information over the optical fiber is restricted by various dispersion phenomenon which further results into inter-symbol interference (ISI). There are numerous alternatives present to resolve this hurdle of dispersion. Unlike other dispersion compensating procedures, electronic dispersion compensators (EDC) which makes use of non-linear and linear equalization approach is an effectual, cost effective and compact dispersion compensating method. This paper is approaching EDC technique for compensation of chromatic dispersion at four distinct bit rates of 25, 30, 40 and 40 Gbps over 120Km of single mode fiber. To Achieve this, a single channel optical system with the help of simulation software i.e., Optisystem is being used for the above-mentioned technique. After exploring their outcomes, another operation of comparing these two-bit rates using pin photodiode and avalanche photodiode has been applied. The simulations showed the optimum photodiode for efficacious dispersion compensation at such a long transmission distance.